Isotherm and Kinetic Studies on the Adsorption Behavior of Metanil Yellow Dyes onto Modified Shrimp Shell-Polyethylenimine (SS-PEI) - Rahmiana Zein; Zulkarnain Chaidir; Zilfa Zilfa; Syiffa Fauzia; Putri Ramadhani (Syarif Hidayatullah State Islamic University, 2022)
The present study investigated the ability of modified shrimp shell by Polyethylenimine (PEI) for enhanced removal of metanil yellow. The modification was carried out using citric acid as a cross linker. The removal of metanil yellow by modified shrimp shell-PEI was conducted by batch method and investigated some parameters affected adsorption including pH, initial dye concentration, and contact time. The optimum conditions were achieved at pH 5, initial dye concentration 1200 mg/L, and contact time 90 minutes. The adsorption isotherm study showed that the adsorption of metanil yellow dye by modified shrimp shell-PEI followed the Langmuir isotherm model with a maximum adsorption capacity (qm) 121.951 mg/g. The kinetic study indicated that the adsorption process suited to the pseudo-second-order model. The characterization results revealed the differences in the adsorbent characteristics before and after the adsorption of metanil yellow dye. The cross-linked PEI onto shrimp shell provided more active sites (amine groups) to bind dye molecules. It can be concluded that modified shrimp shell by PEI has increased its ability in metanil yellow removal.